Strengthening Students’ Character through the Community Service Program (Sekolah Kerja Nyata, SKN) - Vivi Rahmelia; Anik Widiastuti; Agustina Tri Wijayanti; Taat Wulandari (Universitas Pendidikan Ganesha, 2025)
Character education in schools often faces challenges in internalizing values through real-life experiences. Limited student engagement makes character education less meaningful. This study aims to describe the implementation of character education through the Community Service Program (Sekolah Kerja Nyata, SKN) and to identify the values it fosters. Using a descriptive qualitative method, data were collected through in-depth interviews with the principal, supervising teachers, and students. The results show that SKN successfully fostered values such as responsibility, cooperation, social awareness, independence, and religiosity. Students demonstrated improvements in discipline, communication skills, and leadership through participation in social activities. The program aligns with experiential character education approaches that emphasize social interaction as a means of value formation. The study concludes that SKN is an effective model of character education by integrating academic learning and attitude development through direct engagement. SKN also has the potential to be adopted as a co-curricular activity within the new curriculum structure, as it supports cross-disciplinary learning and character development through contextual, project-based approaches. These findings provide a foundation for developing similar programs in other schools to strengthen character formation relevant to real life.